Applicability of Phenolic Profile Analysis Method Developed with RP-HPLC-PDA to some Bee Product - Kara,Yakup (2022)
Abstract In this work, a reverse phase high-performance liquid chromatographic method (RP-HPLC) with photo diode array (PDA) at 4 different wavelengths (250, 280, 320 and 360) for the determination of some polyphenols in some bee products (honey, pollen, and propolis) is developed. The analyses were carried out on C18 column (250 mm x 4.6 mm, 5 µm; GL Sciences), and the gradient program was used with a mobile phase A reservoir with 70% acetonitrile and the B reservoir with 2% acetic acid. The HPLC method was founded that limit of detection was in the range 0.022-0.0908 µg/mL; the limit of quantification was in the range 0.074-0.3027 µg/mL, all calibration curves were linear R2>0.995 within the range, the recovery range was 91.43- 111.37% for 10 ppm and 98.44-101.68% for 40 ppm and relative error levels 0.0330-0.0290 respectively. The developed method was applied to some bee products available on the Turkey market. The study aimed at phenolic profiles of the bee products extracts were revealed by using 25 phenolic standards. The proposed method was optimized, quickly, and simple validated by evaluating the linear range, the limits of detection and quantification, the accuracy, the precious, the repeatability, and recoveries suitable for the phenolic analysis. It is concluded that evaluated and the quantitative determination of the bee products can be made quickly and reliably with the optimized method.